(untitled) (Bangladesh Journal of Medical Science, 2026)
Background Regional mandibular bone quality is a decisive factor in implant treatment planning, but radiographic density alone may not fully reflect the microscopic architecture and biological activity of alveolar bone. This in vitro study evaluated histomorphometric and immunohistochemical variations in bone density across mandibular regions using decalcified specimens. Methods Sixty mandibular bone specimens were obtained from 20 formalin-fixed adult human mandibles and grouped into anterior, premolar, and molar regions (n=20 each). Specimens were decalcified with 10% ethylenediaminetetraacetic acid, paraffin embedded, sectioned, and stained with hematoxylin and eosin and Masson’s trichrome. Histomorphometric variables included cortical thickness, trabecular bone area fraction, trabecular thickness, trabecular separation, and osteocyte density. Immunohistochemistry was performed for osteocalcin, osteopontin, RANKL, and osteoprotegerin. Results The anterior mandible showed the greatest cortical thickness (3.12 ± 0.41 mm) and trabecular bone area fraction (48.6 ± 6.8%), followed by the premolar region (2.61 ± 0.36 mm; 41.9 ± 5.9%) and molar region (2.18 ± 0.33 mm; 35.4 ± 6.2%) (p<0.001). Osteocalcin immunoreactivity was highest anteriorly (72.4 ± 8.1%) and lowest posteriorly (58.7 ± 9.4%) (p<0.001). RANKL expression and RANKL/OPG ratio increased toward the molar region (p=0.003), indicating relatively greater remodeling activity in posterior mandibular bone. Conclusion: Mandibular bone density showed marked regional variation at both structural and cellular levels. These findings support region-specific interpretation of bone quality during implant site preparation and primary stability assessment. Bangladesh Journal of Medical Science Vol. 25. Supplementary Issue-2 (2026), Page : S283-S289